Systematic Overview: Problem Based Learning (PBL) in Mathematics Learning - M. Qomari Hidayat; Rahayu Fitriani (Gema Cendekia Institute, 2025)
Learning (PBL) in mathematics learning at various levels of education during the 2020–2025 period. The main focus of this study is to identify the effectiveness of PBL on the development of students' mathematical skills, the application models used, as well as the supporting factors and obstacles to its implementation This study aims to systematically review the application of Problem Based in the classroom. The method used is Systematic Literature Review (SLR) by searching articles from the Scopus, ScienceDirect, SpringerLink, Taylor & Francis, ERIC, and Google Scholar databases using keywords related to PBL and mathematics education. Articles that meet the inclusion criteria are analyzed through a content analysis approach based on objectives, methods, research context, and findings. The results of the study showed that PBL consistently had a positive effect on improving high-level thinking skills, especially problem solving, mathematical reasoning, creativity, learning independence, and student involvement. However, the effectiveness of PBL is also greatly influenced by the quality of teacher facilitation, authentic problem design, and students' readiness to participate in the inquiry-based learning process. The main obstacles to the implementation of PBL include time constraints, variations in students' initial abilities, and teachers' difficulties in designing contextual problems. Therefore, the success of PBL requires support for teacher training and a more flexible and adaptive curriculum arrangement.